Antagonists of TNFα for recurrent miscarriages: 2 Illustrative cases. (May 2019) - Mekinian, Arsène; Houfflin-Debarge, Véronique; Kolanska, Kamilla; Cohen, Jonathan; Abisror, Noémie; Bornes, Marie; Kayem, Gilles; Fain, Olivier
Abstract: Approximately 1 to 3% of women have recurrent early miscarriages, defined as ≥3 pregnancy losses before 14 weeks of gestation. The immune deregulation and tolerance rupture could be the origin of these miscarriages in at least 30% of these women. Chronic intervillositis of unknown etiology (CIUE) is a rare placental lesion characterized by intrauterine deaths, growth restriction and high recurrence rate. In cases with recurrent obstetrical adverse events and intrauterine deaths, we previously reported the benefit of hydroxychloroquine combination to prednisone. Even few data raised the potential value of TNF antagonists in early recurrent miscarriages, these cases show its potential value in the setting of recurrent refractory chronic intervillositis and unexplained miscarriages.